SEBARAN BAHANG DI PERMUKAAN BOLA DUA DIMENSI MELALUI PENDEKATAN KERNEL - , AL HARUN TAATE, S.Si, Dr.rer.nat. Muh. Farchani Rosyid ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Heat kernel is the fundamental solution of the diffusion equation. The heat equation is constructed to explain types of physical phenomena (physical quantity, vector or scalar) that propagates in the medium due to the concentration gradient. Medium involved in our case here such as Riemannian manifold, that are the surface of a compact and uniform spherical. Therefore, the heat kernel formulated is related with metric space. If there are any innitial accumulation in the surface points of the spherical, then at the same is known the profile distribution of heat at any other point or in the entire region of the surface spherical. Different from the space ô2 where heat decays and disappears with time, the distribution of heat on the surface of spherical is showing feedback process to achieved a state of nature equally. Reversal phenomenon influenced by medium compact topology. Sharpness of the heat distribution affected by the value of the diffusion constant of physical quantities (properties) associated, obtained through an experimentaly investigation. Initial accumulation can be either contents or discrete quantities on the surface of spherical or the geodesic circle on the surface of spherical.